The sixtieth anniversary of describing scientific background for the pelvic floor muscle rehabilitation - Paszkowski, Tomasz; Radomański, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Sixty years after the scientific background of the pelvic floor muscle rehabilitation has been described by Arnold Kegel, this method undergoes a renaissance giving many patients an opportunity to fight such important health problems as pelvic organ prolapse and/or urinary incontinence. This paper reviews the published up-to-date data on the role of pelvic floor muscle exercise in modern gynecological practice.